Safety management systems and their origins : insights from the aviation industry - Bieder, Corinne (CRC Press / Taylor & Francis Group, 2023)
Safety Management Systems and their Origins: Insights from the Aviation Industry presents different perspectives on SMS to better decode what it means as a safety approach and what it implicitly conveys beyond safety.The book uses the aviation industry as a basis for analyzing where the SMS stands in terms of safety enhancement. Through a socio-historical analysis of how SMSs emerged and spread across high-risk industries and countries, the book also explains the other stakes underpinning this new approach to safety management.Features:Explores SMS as it is implemented in aviation based on examples from several countries and regions, namely the UK, USA, and Australia.Presents a socio-historical analysis of how SMSs emerged in high-risk industries.Provides insights to explain the existing limitations of SMS.Proposes new avenues to reach beyond the limitations of SMS.Discusses the COVID-19 pandemic within the framework of risk analysis.The book is intended for safety professionals and regulators, as well as graduate students and researchers in safety science and engineering